(untitled) (Research, Society and Development, 2022)
The linear production model based on extract, produce, use and dispose is reaching its limit due to environmental impacts and scarcity of resources. The circular economy appears in opposition to this production model, with principles based on eliminating waste and pollution, keeping materials in use and recovering natural systems. Industrial symbiosis is indicated to put into practice the principles of the circular economy, through the creation of synergies and mutual cooperation between industries, where they can share resources and reuse production residues. In order to understand how industrial symbiosis can contribute to the implementation of the circular economy, this work assessed the degree of maturity of industrial symbiosis in a flat glass production company, through the indicator degree of maturity of industrial symbiosis, which lists the seven barriers of industrial symbiosis against the five stages of maturity. To quantify the degree of maturity of the industrial symbiosis, an Equation was created, an original production of this work, which made it possible to identify that the company currently has 28,5% of the degree of maturity, making it possible to identify what can be improved, facilitating the decision-making process.